Eelgrass beds can mitigate local acidification and reduce oyster malformation risk in a subarctic lagoon, Japan: A three-dimensional ecosystem model study. (May 2022) - Abe, Hiroya; Ito, Minako Abe; Ahn, Hyojin; Nakaoka, Masahiro
Abstract: It is well known that ocean acidification (OA) inhibits growth of marine calcifying organisms. Therefore, the adverse effects of acidification on marine ecosystems and aquaculture, such as oyster farming, are of concern. Since eelgrass beds in neritic areas have a high potential for carbon assimilation, this study focuses on local scale mitigation of OA effects. Using a three-dimensional lower-trophic system ecosystem model, we modeled nitrogen and carbon cycles, and the dynamics of carbonate parameters in a subarctic shallow lagoon and bay, where nitrogen availability limits the photosynthesis of primary producers. Simulation of the present conditions allowed reproduction of spatiotemporal variations in water quality and, by assuming future environmental changes quantitatively, revealed that the progress of OA significantly elevated the probability of shell malformation in juvenile oysters. The results represent the spatiotemporal variations in carbonate parameters inside and outside eelgrass beds and enable the evaluation of the alleviation effect on local acidification by the presence of a dense eelgrass bed. Our study shows that in the absence of the eelgrass bed scenario, the effect of OA on oysters became more remarkable. The simulations revealed that maintaining eelgrass beds is essential to mitigate the effects of acidification on oysters. Highlights: An ecosystem model representing carbonate systems in a lagoon was developed. The effect of ocean acidification on oyster malformation was evaluated. Simulation under the absence of eelgrass bed was also performed. The model could reproduce the spatiotemporal variations of the observed values. Eelgrass beds mitigate the adverse effects of acidification on oyster growth.